Maximum Power Tracking System Based on Power Electronic Topology for Wind Energy Conversion System Applications - Hussain, M.; Baloch, M. H.; Memon, A. H.; Pathan, N. K. (Engineering, Technology & Applied Science Research, 2018)
Wind energy has emerged as a dominant alternative power generation source. Conventional energy resources are depleting and their increasing cost cannot be ignored. Wind energy has taken an important role in replacing fossil fuels and nuclear energy. However, optimal exploitation of wind energy systems has remained a thought-provoking problem due to the nonlinear behavior of the wind speed. Distribution generation system and isolated micro-grid (MG) are mainly used in a wind energy system in order to utilize maximum potential of wind through the maximum power tracking algorithm based on DC-DC boost power electronic converter. In this paper, authors propose a technique which is effectively workable, highly reliable, of low cost and induces less mechanical stress on the wind generator system (WGS). Experimental results of the proposed system verify that the effectiveness near optimal WGS output power increased approximately up to 50%. Thus, better exploitation of the available wind power is obtained under low wind speeds.